Multi-phase homogenization procedure for estimating the mechanical properties of shot-earth materials. (1st September 2022) - Bacciocchi, M.; Savino, V.; Lanzoni, L.; Tarantino, A.M.; Viviani, M.
Abstract: The paper proposes an analytical homogenization procedure to predict the overall elastic properties of shot-earth, a sustainable composite material made of excavated soil, aggregates and, if needed, a binder for stabilization. A multi-step methodology based on the Mori–Tanaka approach is used to account for the stabilized soil inclusions. This approach is proposed in order to shorten the mix-design procedures and readily provide to the structural engineers a set of mechanical properties of the shot-earth components to be used in the early design phases, when the construction field is not open yet and excavation of the site has not begun. The analytical results were successfully validated through an experimental campaign.